FINANCIAL INCLUSION, POPULATION QUALITY LEVEL, POVERTY, AND UNEMPLOYMENT ON ECONOMIC GROWTH - Aryani, Dwi; Masruki, Rosnia; Bunyamin, Bunyamin; Rorimpandey, Thalia; Istutik, Istutik (Faculty of Economics and Business, University of Pasundan, 2024)
The purpose of this research are to analyse the effect of financial inclusion and population quality level on economic growth with poverty and unemployment as intervening variables. The research method used in this study is a quantitative descriptive analysis approach. The independent variables are financial inclusion, population quality level, poverty, unemployment, and the dependent variable is economic growth. The total data employed is 1020 which was taken from the Central Agency of Statistic (BPS) and the Financial Service Authority (OJK) in year 2016-2021. The data analysis method used is Partial Least Square with Structural Equation Modelling and bootstrapping method. The results showed that financial inclusion does not have an effect on economic growth, poverty and unemployment. Poverty and unemployment cannot mediate the correlation between financial inclusion and level of population quality on economic growth. Unemployment has a positive effect on poverty.A slower economic growth and poverty in Indonesia are still a crucial problem that must be solved, therefore this study gives essential implications to provide data for policymakers such as the OJK that has important role on encouraging financial inclusion and economic growth; as well as BPS in reducing poverty and unemployment; and to enrich literature and theory.